Depression, anxiety, and stress among students of Sriwijaya University - Habibah, Umrohtul; Syakurah, Rizma Adlia; Ikhsan, Diyaz Syauki; Zulissetiana, Eka Febri; Aini, Syarifah (Indigenous, 2021)
Abstract. The prevalence of Major Depressive Disorder (MDD) among students was the highest (18.5%), followed by anxiety (16.7%). Psychosocial stressors and academic pressure on students require them to be able to adjust themselves in order to cope with the mental stress that occurs. The aims to descriptions of mental health, especially depression, anxiety, and stress in students. An analytic observational study with a cross-sectional design used. As much 1564 students from 10 faculties filled out the DASS-42 questionnaire distributed via social media in January 2020−24 August 2020. The analyzed using chi-square, Mann Whitney, and binary logistic regression with significance of 0.05. Students who have a risk to depression, anxiety, and steress are 46%, 74.2%, and 57.9%. There is a significant relationship between the incidence of depression with GPA, faculty, semester and place of residence (p0.05). Gender, faculty, and religion factors associated with the anxiety (p0.05). While the gender, place of residence and faculty associated with stress (p0.05). History of chronic illness and family history of mental disorders influenced the depression, anxiety disorders, and stress (p 0.001). Mostly, Sriwijaya University students have an increase in depression, anxiety, and stress, especially during the Covid-19 pandemic. The gender, semester, marital status, history of chronic disease, and a history of mental disorders in the family affect the incidence of depression, anxiety, and stress. The mean GPA of students with a tendency to depression, anxiety, and stress was lower by ± 0.03 points. The university stakeholders needs to implement mental health interventions to maximize student potential.Keywords: Mental disorders; college students; depression; anxiety; stress